29.5k views
5 votes
How to solve
6r+7=13+7r

User Pguetschow
by
5.7k points

2 Answers

1 vote
6r+7=13+7r
-6r. -6r
7=13+1r
-13 -13
-6/1=1/1r
-6=r
User Tasmia
by
5.3k points
3 votes
Hello there! So for this equation, we are solving for the value of r. First off, let's subtract 6r from both sides. 6r - 6r cancels out. 7r - 6r is 1r or just simply r. That gets us 7 = 13 + r. Subtract 13 from both sides. The 13 on the right side cancels out. 7 - 13 is -6. -6 = r is left. There is nothing else to divide, so we have our value, but let's check it by plugging in -6 as r.
6 * -6 is -36. -36 + 7 is -29. 7 * -6 is -42. -42 + 13 is -29. -29 = -29. There. r = -6.
User Zapnologica
by
5.9k points